PERLINDUNGAN HUKUM BAGI KONSUMEN YANG MELAKUKAN IZIN PENUNDAAN PEMBAYARAN ANGSURAN - Soraja, Alga; Prasetyawati, Endang (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2022)
One itype of financing business in a financial institution is consumer financing. Consumer financing is a business entity that carries out financing activities for the procurement of goods based on consumer needs with an installment or periodic payment system by consumers. This situation encourages the importance of the existence and development of consumer finance institutions. The public's choice of consumer financing institutions is due to the need for fast service, uncomplicated procedures, and easy-to-fulfill requirements.